Biomimetic Implant Surface Functionalization with Liquid L-PRF Products: In Vitro Study. (8th May 2018) - Lollobrigida, Marco; Maritato, Manuela; Bozzuto, Giuseppina; Formisano, Giuseppe; Molinari, Agnese; De Biase, Alberto
Abstract : Objective . Platelet-rich fibrin (PRF) clots and membranes are autologous blood concentrates widely used in oral surgical procedures; less is known, however, about the liquid formulations of such products. The aim of this in vitro study is to assess the behavior of different implant surfaces when in contact with two liquid leucocyte- and platelet-rich fibrin (L-PRF) products. Methods . Six commercial pure titanium discs, of 9.5 mm diameter and 1.5 mm thickness, were used. Three of these samples had a micro/nano-rough surface; three were machined. Three different protocols were tested. Protocols involved the immersion of the samples in( 1 ) a platelets, lymphocytes, and fibrinogen liquid concentrate (PLyF) for 10 minutes, ( 2 ) an exudate obtained from L-PRF clots rich in fibronectin and vitronectin for 5 minutes, and( 3 ) the fibronectin/vitronectin exudate for 2 minutes followed by immersion in the PLyF concentrate for further 8 minutes. After these treatments, the samples were fixed and observed using a scanning electron microscope (SEM). Results . Under microscopic observation, ( 1 ) the samples treated with the PLyF concentrate revealed a dense fibrin network in direct contact with the implant surface and a significant number of formed elements of blood;( 2 ) in the samples treated with the fibronectin/vitronectin exudates, only a small number of white and red blood cells were detectable; and( 3 ) in samples exposed to the combined treatment, there was an apparent increase in the thickness of the fibrin layer. When compared to the machined surface, the micro/nano-rough samples showed an overall increased retention of fibrin, leading to a thicker coating. Conclusions . Liquid L-PRF products promote the formation of a dense fibrin clot on micro/nano-rough implant surfaces in vitro. The adjunctive treatment of surfaces with the fibronectin/vitronectin exudate could provide support to contact of the fibrin with the surface, though it is not essential for the clot formation. Further studies are necessary to better elucidate the properties and benefits of liquid L-PRF products.